2010
DOI: 10.1111/j.1939-1676.2010.0499.x
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Cerebellar Degeneration in Scottish Terriers

Abstract: Background: Hereditary cerebellar degeneration is described in several dog breeds. This heterogeneous group of diseases causes cerebellar ataxia associated with cerebellar cortical degeneration.Objective: To report the clinical and histopathological features, and describe the mode of inheritance of hereditary cerebellar degeneration in Scottish Terriers.Animals: Sixty-two affected dogs recruited through the Scottish Terrier Club of America. Materials and Methods: Prospective, observational study: Owners of aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 27 publications
2
35
0
4
Order By: Relevance
“…This is in contrast to breeds where a neonatal, rapidly progressive phenotype is seen, such as the Beagle and Rhodesian Ridgeback [3, 13], and those with a later onset and more slowly progressive condition typified by CCD in Gordon Setters and Old English Sheepdogs [15]. Similar to reports of canine CCD seen in other breeds [12, 16], the observed clinical signs in the HV were referable to diffuse cerebellar dysfunction, with both dogs displaying a marked hypermetric, dysmetric ataxia, with marked truncal sway and intention tremor, as well as bilateral menace deficits with normal vision. Although they remained ambulatory, both dogs demonstrated a progressive clinical course over a short period of around two months, to the point that their owners elected for euthanasia on humane grounds due to their poor quality of life.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…This is in contrast to breeds where a neonatal, rapidly progressive phenotype is seen, such as the Beagle and Rhodesian Ridgeback [3, 13], and those with a later onset and more slowly progressive condition typified by CCD in Gordon Setters and Old English Sheepdogs [15]. Similar to reports of canine CCD seen in other breeds [12, 16], the observed clinical signs in the HV were referable to diffuse cerebellar dysfunction, with both dogs displaying a marked hypermetric, dysmetric ataxia, with marked truncal sway and intention tremor, as well as bilateral menace deficits with normal vision. Although they remained ambulatory, both dogs demonstrated a progressive clinical course over a short period of around two months, to the point that their owners elected for euthanasia on humane grounds due to their poor quality of life.…”
Section: Discussionmentioning
confidence: 61%
“…CCD typically causes slowly progressive clinical signs related to diffuse cerebellar dysfunction, including a dysmetric and hypermetric cerebellar ataxia, intention tremors, menace response deficits and signs of central vestibular dysfunction, including nystagmus and loss of balance [12, 16]. Age of onset of clinical signs and the rate of progression vary between breeds, ranging from neonatal, as reported in Beagles and Rhodesian Ridgebacks [3, 13], and early onset from weeks to months of age in the majority of breeds [2, 6, 8, 9, 14, 16], up to adult-onset at months to years of age with a slower progression, seen in Old English Sheepdogs, Gordon Setters and Scottish Terriers [12, 15, 17]. …”
Section: Introductionmentioning
confidence: 99%
“…40 The main histopathological finding on evaluation of the cerebellum of diseased dogs is loss of Purkinje neurons with thinning of the granular and molecular layers. 40 Quantification of Purkinje neurons in our study confirmed that there is significant loss of these neurons in affected dogs compared with control dogs. More specifically, Purkinje neuron degeneration in the vermis of the cerebellum was more profound dorsally, especially at the convexity of the folia, than ventrally, but there was no rostrocaudal gradient.…”
Section: Discussionmentioning
confidence: 99%
“…1,39 The number of corpora amylacea has been reported to increase in association with several other neurodegenerative disorders, in which the polyglucosan body does not appear to be the primary cause of neurodegeneration. 22,44 To determine whether the polyglucosan bodies previously described in affected Scottish terriers 40 were a consequence of their neurodegenerative disease or simply of aging, we quantified the distribution of these bodies and described their staining characteristics and ultrastructural features in both control and affected dogs. Although the density of polyglucosan bodies in affected and age-matched control dogs was not significantly different, in the affected dogs, contrary to expectations, there were significantly more bodies in the ventral half of the cerebellum with surviving Purkinje neurons than in regions in which the Purkinje neuron population was depleted.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the familial syndromes reported thus far are inherited by an autosomal recessive mode including the Old English Sheepdog (OES), 11,12 Gordon Setter, 12,13 Scottish Terrier, 14 Finnish Hound, 15 Rhodesian Ridgeback, 16 Beagle, 17 and Australian Kelpie. 18 An X-linked disorder has been reported in the English Pointer.…”
Section: Cerebellar Cortical Degenerationmentioning
confidence: 99%